1993
DOI: 10.1056/nejm199305203282001
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis and the Risk of Pancreatic Cancer

Abstract: The risk of pancreatic cancer is significantly elevated in subjects with chronic pancreatitis and appears to be independent of sex, country, and type of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
456
3
20

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,539 publications
(489 citation statements)
references
References 25 publications
10
456
3
20
Order By: Relevance
“…The patients' mean age was 52.98 (±9.40) years; subtracting mean disease duration from mean age confirms data published by Lowenfels et al 21 , who found that the mean age of their patients at diagnosis of chronic pancreatitis was 44.6 years. Yet Mullhaupt et al 22 found a mean age at alcoholic chronic pancreatitis onset of 36 years in a sample of 265 patients.…”
Section: Discussionsupporting
confidence: 87%
“…The patients' mean age was 52.98 (±9.40) years; subtracting mean disease duration from mean age confirms data published by Lowenfels et al 21 , who found that the mean age of their patients at diagnosis of chronic pancreatitis was 44.6 years. Yet Mullhaupt et al 22 found a mean age at alcoholic chronic pancreatitis onset of 36 years in a sample of 265 patients.…”
Section: Discussionsupporting
confidence: 87%
“…The risk of pancreatic cancer is known to increase with the duration of CP [39], therefore follow up imaging in CP is recommended [40]. Two cases of pancreatic cancer were identified in our cohort, thus supporting routine pancreatic imaging when PEI is diagnosed.…”
Section: Imagingsupporting
confidence: 66%
“…The inherited basis of B10-20% of familial pancreatic cancers has been identified and is reflected largely in germline mutations in the BRCA2 gene (Goggins et al, 1996;Ozcelik et al, 1997;Hahn et al, 2003) (The Breast Cancer Linkage Consortium, 1999;Murphy et al, 2002). Germline mutations in the p16 (Goldstein et al, 1995;Lynch et al, 2000;Vasen et al, 2000;Bartsch et al, 2002), FANCC (van der Heijden et al, 2003;Rogers et al, 2004), FANCG (van der Heijden et al, 2003;Rogers et al, 2004), PRSS1 (Lowenfels et al, 1993(Lowenfels et al, , 1997, STK11 (Giardiello et al, 2000;Lim et al, 2004), and hMLH1 (Yamamoto et al, 2001) genes are infrequent causes of familial pancreatic cancer and are associated with a number of cancer syndromes, including familial multiple mole melanoma (FAMMM), hereditary pancreatitis, hereditary nonpolyposis colon cancer, and Peutz-Jeghers syndrome. In addition, germline BRCA2 mutations are observed in B5% of patients with apparently sporadic pancreatic cancer, that is, patients who do not appear to have an inherited predisposition to pancreatic or breast/ovarian cancer (Goggins et al, 1996;Ozcelik et al, 1997;The Breast Cancer Linkage Consortium, 1999;Figer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%